Urbanization Shapes the Ecology and Evolution of Plant-Arthropod Herbivore Interactions - Miles, Lindsay S.; Breitbart, Sophie T.; Wagner, Helene H.; Johnson, Marc T. J. (Frontiers in Ecology and Evolution, 2019)
Urbanization is quickly changing natural and agricultural landscapes, with consequences for the herbivorous arthropods dwelling in or near cities. Here, we review the evidence for the effects of urbanization on the ecology and evolution of plant-herbivore interactions. We first summarize how abiotic factors associated with urbanization affect the ecology and evolution of herbivorous arthropods. Next, we explore how urbanization affects plant-herbivore interactions, by considering how urban environments may disrupt top-down and bottom-up ecological processes that affect herbivory. Abiotic changes in the urban environment, such as the urban heat island effect, have caused shifts in phenology for some herbivorous arthropods. Other abiotic changes in urban areas, including water availability, pollution, and habitat fragmentation, have resulted in changes to physiology, behavior, and population abundance. Native species richness tends to decline in urban areas, however, changes in abundance appear to be species specific. These shifts in ecology suggest that urbanization could affect both adaptive and non-adaptive evolution of herbivorous arthropods and their host plants in urban environments. However, plant-herbivore interactions may be dramatically altered if either arthropods or plants are unable to tolerate urban environments. Thus, while some species can physiologically acclimate or genetically adapt to the abiotic urban environment, the biotic interactions may cause many species to decline. We conclude with suggestions for future research to advance our understanding of how urbanization alters the ecology and evolution of plant-herbivore interactions.